A novel automated heat-pipe cooling device for high-power LEDs. (25th January 2017) - Xiao, Chengdi; Liao, Hailong; Wang, Yan; Li, Junhui; Zhu, Wenhui
Graphical abstract: Highlights: An automatic cooling device was firstly integrated with microcontroller, heat pipe and fan. Substrate temperature of high-power LEDs can be controlled automatically and be protected safely. LED junction temperature can be maintained at a suitable range. Total power consumption is less than 1.58 W. It is a very promising tool for the heat dissipation of high-power LEDs. Abstract: In order to develop the thermal management of high-power LEDs, an automatic cooling device was firstly integrated with a microcontroller, heat pipes and fan. According to the experimental results, it was found that the substrate temperature of the high-power LEDs could be controlled automatically, and it could be kept in a relative low range to protect the LEDs, which contributes a better performance and longer lifetime of LED. A numerical model of the cooling system was established and its effectiveness was verified by experimental results. The simulation results show that the LED junction temperature can be maintained at a suitable range. Thus, the thermal resistances Rsa (from the heat sink to the ambient) and Rja (from the LED chip to the ambient) of the cooling system are 0.373 °C/W and 5.953 °C/W at 12 W, respectively. In addition, increasing the number of heat pipes & cooling fins is an effective method to improve heat transfer of the cooling system. The proposed cooling system, whose total power consumption is less than 1.58 W, is a very promising tool for the heat dissipation of high-power LEDs.